Autecological studies of Drosera linearis, a threatened sundew species - (:unkn) unknown (My University, 1984)
The linear-leaf sundew has been extirpated from several stations at the southern edge of Its range. Cedarburg Bog is believed to harbor the largest of the remaining southern colonies of this species. Drosera linearis has a lower reproductive output at Cedarburg Bog than at other sites, and produces fewer seeds per plant than the three sundew species which share its range. The population studied at Cedarburg Bog declined in population size and reproductive output from 1980 to 1982, and revealed characteristics associated with high rates of local extinction. Populations experienced rapid turnover of individuals, and population size was closely coupled to the size of the previous year's seed crop. Sustained flooding in the flarks of the patterned fen further decreased population stability. The species may have persisted at Cedarburg Bog because the patterned fen is sufficiently large to allow the recolonization rate to keep pace with the rate of local extinction.
Keywords: Drosera linearis; linear-leaf sundew; Cedarburg Bog